Effect of clove (Syzygium aromaticum) and seaweed (Kappaphycus alvarezii) water extracts pretreatment on lipid oxidation in sun‐dried sardines (Rastrineobola argentea) from Lake Victoria, Tanzania. Issue 4 (27th February 2019) - Chaula, Davis; Laswai, Henry; Chove, Bernard; Dalsgaard, Anders; Mdegela, Robinson; Jacobsen, Charlotte; Hyldig, Grethe
Abstract: Small indigenous fish species play a significant role in food and nutritional security of poor communities in developing countries. Sardines ( Rastrineobola argentea ) are fish species of Lake Victoria known to be a good source of health‐promoting omega‐3 fatty acids. Open sun drying is a common and traditional sardine processing and preservation method. Sun‐dried products suffer from characteristic off‐flavor due to lipid oxidation which discourage product consumption and limit diversification. This study investigated the use of clove ( Syzygium aromaticum ) and seaweed ( Kappaphycus alvarezii) water extracts as natural antioxidants to impede lipid oxidation in sun‐dried sardines. Lipid oxidation was assessed by peroxide value, volatile secondary oxidation products, and fatty acid profiles. The antioxidant capacity of extracts was evaluated by total phenolic content, 1, 1‐diphenyl‐2‐picrylhydrazyl (DPPH) radical scavenging, and iron (Fe 2+ ) chelating ability. Results showed that 5, 10, and 20 g/L clove extracts significantly reduced peroxidation in sun‐dried sardines by 38.7%, 54.6%, and 56%, respectively. Clove extracts resulted in higher retention of omega‐3 fatty acids and lower concentrations of secondary lipid oxidation products as opposed to seaweed counterpart. This research has demonstrated feasibility of pretreating whole, omega‐3‐rich small sardines with natural antioxidants to avert lipid oxidation during sun drying. Abstract : Clove water extract reduced peroxidation in sun‐dried sardines. Clove water extract resulted into higher retention of omega‐3 fatty acids in sun‐dried sardines. Red seaweed water extracts showed pro‐oxidant activity in sun‐dried sardines.